26 Distribution of high sensitivity troponin levels in consecutive, unselected patients in the emergency department and relationship to in-hospital mortality. (17th July 2020) - Hinton, Jonathan; Mariathas, Mark; Gabara, Lavinia; Nicholas, Zoe; Allan, Rick; Ramamoorthy, Sanjay; Mamas, Mamas; Mahmoudi, Michael; Cook, Paul; Curzen, Nick
Abstract : Introduction: The introduction of high-sensitivity troponin assays has facilitated pathways to rapidly exclude myocardial infarction (MI) in patients presenting to the emergency department (ED) with chest pain. However, hs-cTn concentrations above the manufacturer-supplied upper limit of normal (ULN) are frequently detected in patients presenting to ED, despite only a small proportion having a type 1 MI. Furthermore, there is also increasing evidence that hs-cTn concentrations may act as a biomarker of cardiovascular risk in patients outside the context of acute coronary syndrome. In the current study, we report the distribution of hs-cTn in the subpopulation of CHARIOT who attended ED, in whom the assay was taken regardless of whether there was a clinical indication. Our aim was to test the hypothesis that hs-cTn may be a biomarker for in-hospital mortality, irrespective of the indication for its measurement. Method: The study included 5708 consecutive patients attending ED in a single centre. In all cases hs-cTnI was measured either as requested by the clinical team, or as part of the study, in which case both the clinical team and the patient were unaware of the test. Basic demographics were available from the original CHARIOT study and both the electronic clinical record and coding data were interrogated to ascertain the clinical outcome. Results: 491 (8.6%) patients had hs-cTnI concentrations above the manufacturer's ULN. There were 4157 (72.8%) patients in whom the hs-cTnI was performed solely as part of the study, with 309 (7.4%) of these above the ULN. Five patients died in ED. Of the remaining patients, 3603 (63.2%) were admitted to hospital. The rate of admission increased with rising hs-cTnI concentrations (table 1 ). A cardiovascular diagnosis was the most frequent discharge diagnosis in those with a hs-cTnI above the ULN. However, a neurological condition was most common in the patients in whom the test was only performed as part of the study. Increasing hs-cTnI concentrations were associated with increasing in hospital mortality regardless of whether the hs-cTnI was requested for clinical reasons or not (figures 1 & 2 ). Furthermore, hs-cTnI demonstrated good discriminative ability for in-patient mortality (area under receiver operator curve 0.834). Hs-cTnI above the ULN remained an independent predictor of mortality on multivariate analysis. The median length of stay was also associated with increasing hs-cTnI concentrations. Conclusion: In consecutive patients presenting to ED, hs-cTnI elevation is common. Furthermore, increasing hs-cTnI concentrations are associated with increased admission rates from ED, longer in-patient stays and higher in-hospital mortality. Hs-cTnI may therefore represent a biomarker for in hospital outcomes in these patients. Conflict of Interest: Unrestricted research grant from Beckman Coulter (who had no role in the design, analysis, interpretation of the study)